2016
DOI: 10.1123/pes.2014-0218
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Actical and ActiGraph Approach to Measuring Young Children’s Physical Activity Levels and Sedentary Time

Abstract: Young children's activity and sedentary time were simultaneously measured via the Actical method (i.e., Actical accelerometer and specific cut-points) and the ActiGraph method (i.e., ActiGraph accelerometer and specific cut-points) at both 15-s and 60-s epochs to explore possible differences between these 2 measurement approaches. For 7 consecutive days, participants (n = 23) wore both the Actical and ActiGraph side-by-side on an elastic neoprene belt. Device-specific cut-points were applied. Paired sample t t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
(58 reference statements)
3
24
0
Order By: Relevance
“…It has been reported that the amount of daily life activity for the motor-functional evaluation of healthy children and pediatric diseases3,4,5,6 ) can be monitored using an actigraph. Furthermore, the amount of activity recorded by an actigraph has been used as the main outcome index to reflect the amount of physical activity in the home environment of patients with DMD6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the amount of daily life activity for the motor-functional evaluation of healthy children and pediatric diseases3,4,5,6 ) can be monitored using an actigraph. Furthermore, the amount of activity recorded by an actigraph has been used as the main outcome index to reflect the amount of physical activity in the home environment of patients with DMD6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…As little movement of the arms or hips occurs during activities such as cycling on a tricycle, this activity is classified as MVPA according to the OSRAC‐P, but may be classified as LPA according to accelerometry. Similar issues have been highlighted by prior research when differentiating light PA from SB, and light PA from MVPA . Vale et al stated that this difficulty can be due to the type of activities that can be included in free play.…”
Section: Discussionmentioning
confidence: 67%
“…There is also a lack of clarity as to which accelerometer cut points provide the most accurate assessment of both PA and SB in free-living conditions. 9 Additionally, understanding which epoch length might be preferable to capture the sporadic and short burst nature of pre-schoolers PA would be beneficial in guiding researchers in the analysis of accelerometer data. 10 There is also debate which location may be optimal when assessing PA in pre-schoolers.…”
Section: Dobell Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of 3 ×24HR with a FFQ outlined here is an example of an approach that can be applied not only to dietary methodology but also to other methods used in nutrition practice and research, which are commonly assessed for agreement using BA methodology. These include comparing resting energy expenditure prediction equations to indirect calorimetry (39)(40)(41)(42) , bioelectrical impedance analysers to dual energy x-ray absorptiometry for assessing body composition (43)(44)(45)(46) and in validating physical activity assessment tools (47)(48)(49) . In summary, we have introduced an equivalence approach to be used in conjunction with the BA method in order to encourage clinicians to establish up front what constitutes a clinically meaningful difference between the two methods being considered.…”
Section: Discussionmentioning
confidence: 99%